2021
DOI: 10.3390/v13040627
|View full text |Cite
|
Sign up to set email alerts
|

Vaccine Development for Severe Fever with Thrombocytopenia Syndrome

Abstract: Severe fever with thrombocytopenia syndrome (SFTS), which is caused by SFTS virus (SFTSV), is a tick-borne emerging zoonosis with a high case-fatality rate. At present, there is no approved SFTS vaccine, although the development of a vaccine would be one of the best strategies for preventing SFTS. This article focused on studies aimed at establishing small animal models of SFTS that are indispensable for evaluating vaccine candidates, developing these vaccine candidates, and establishing more practical animal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 66 publications
0
14
0
Order By: Relevance
“…Song et al demonstrated the neutralization activity of Gn-specific antibodies from convalescent patients [7]. In addition, a recombinant viral vector-based vaccine expressing the SFTSV glycoprotein or DNA vaccine encoding the SFTSV glycoprotein has been reported as a vaccine candidate for SFTS [18]. If further evidence of a protective effect of anti-Gn-specific IgG is provided by the neutralizing antibody assay, our Gn-specific antibody response data might be helpful in choosing a potential donor of convalescent plasma therapy or developing a vaccination strategy.…”
Section: Discussionmentioning
confidence: 99%
“…Song et al demonstrated the neutralization activity of Gn-specific antibodies from convalescent patients [7]. In addition, a recombinant viral vector-based vaccine expressing the SFTSV glycoprotein or DNA vaccine encoding the SFTSV glycoprotein has been reported as a vaccine candidate for SFTS [18]. If further evidence of a protective effect of anti-Gn-specific IgG is provided by the neutralizing antibody assay, our Gn-specific antibody response data might be helpful in choosing a potential donor of convalescent plasma therapy or developing a vaccination strategy.…”
Section: Discussionmentioning
confidence: 99%
“…While Phase 1 trials in humans have not yet been conducted for other phleboviruses, several approaches for SFTSV have been explored in animal models with varying degrees of success 66 . A DNA vaccine encoding full‐length Gn, Gc, N, NS, and RdRp genes of SFTSV generated both neutralizing antibodies and a T cell response that was able to protect from lethal challenge in a ferret challenge model 67 .…”
Section: Phlebovirus Vaccine Developmentmentioning
confidence: 99%
“…Ferret and other animal models of some human phenuivirid diseases have been developed, which are valuable in developing therapeutics and preventive measures [14,154]. Live-attenuated virus-based, viral vectorbased, and DNA-based vaccines for SFTS, which are expected to be used for humans and companion dogs and cats, have been under investigation, and their efficacy has been confirmed using animal models [155], but none of them have entered clinical trials.…”
Section: Control Of Pathogenic Phenuivirusesmentioning
confidence: 99%
“…10,127 Live-attenuated virusbased, viral vector-based, and DNA-based vaccines for SFTS, which are expected to be used for humans and companion dogs and cats, have been under investigation, and their efficacy has been confirmed using animal models. 128 RVFV vaccines have been used in animals in endemic regions, and human RVFV vaccines have entered clinical trials. 129,130 Inactivated RVF candidate vaccine requires three doses and the live-attenuated MP-12 candidate vaccine requires only one dose to induce protective immunity.…”
Section: Control Of Pathogenic Phenuivirusesmentioning
confidence: 99%